2016
DOI: 10.1681/asn.2016020169
|View full text |Cite
|
Sign up to set email alerts
|

Intercalated Cell Depletion and Vacuolar H+-ATPase Mistargeting in an Ae1 R607H Knockin Model

Abstract: Distal nephron acid secretion is mediated by highly specialized type A intercalated cells (A-ICs), which contain vacuolar H-ATPase (V-type ATPase)-rich vesicles that fuse with the apical plasma membrane on demand. Intracellular bicarbonate generated by luminal H secretion is removed by the basolateral anion-exchanger AE1. Chronically reduced renal acid excretion in distal renal tubular acidosis (dRTA) may lead to nephrocalcinosis and renal failure. Studies in MDCK monolayers led to the proposal of a dominant-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…One study [19] showed that retention of heterologous AE1 p.R589H in the endoplasmic reticulum of polarized Madin-Darby canine kidney cells, along with co-retention of co-expressed wild-type AE1, suggesting dominant negative trafficking defects. However, a recent study [20] with an Ae1 p.R607H knock-in mouse model (which corresponds to human AE1 p.R589H) showed that both heterozygous and homozygous knock-in mice exhibited incomplete dRTA (less severe in heterozygotes than in homozygotes). Interestingly, the targeting of Ae1 p.R607H to the basolateral plasma membrane of the α-intercalated cells was normal, as was transport activity in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…One study [19] showed that retention of heterologous AE1 p.R589H in the endoplasmic reticulum of polarized Madin-Darby canine kidney cells, along with co-retention of co-expressed wild-type AE1, suggesting dominant negative trafficking defects. However, a recent study [20] with an Ae1 p.R607H knock-in mouse model (which corresponds to human AE1 p.R589H) showed that both heterozygous and homozygous knock-in mice exhibited incomplete dRTA (less severe in heterozygotes than in homozygotes). Interestingly, the targeting of Ae1 p.R607H to the basolateral plasma membrane of the α-intercalated cells was normal, as was transport activity in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, NH 4 + becomes the molecular readout of efficient distal acid secretion. This mechanism is maximized during acidosis, where not only the abundance of vH + ATPase, but also the number of A-IC is increased in the inner stripe of the outer medulla [8] . This is the rationale for using NH 4 Cl to evocate a maximal urinary acidification.…”
Section: Renal Acidification Mechanisms: From Molecular Mechanisms Tomentioning
confidence: 99%
“…To recapitulate a mouse model of AE1-dependent dRTA, we recently generated a transgenic mouse expressing one of the most common mutations of the AE1 gene, namely R589H AE1, corresponding to the R607H mutation in mouse AE1 [8] . As humans, these mice do not present RBC abnormalities, but they exhibit incomplete unmasked dRTA when they are challenged with an NH 4 Cl load.…”
Section: Loss Of Function Mutations Of Ae1 Cause Drtamentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with gene mutations in kidney anion exchanger 1 (kAE1) 5,6 caused by decrease in anion exchange thus hinder trafficking and regulation of V-type ATPase, venturing acidification of lysosomes. 7 In a case report, down syndrome was associated hypothyroidism and renal acidosis, with antithyroid peroxidase antibodies positive and with treatment of hypothyroidism, symptoms of acidosis resolved. 8 A case series of periodic paralysis, otosclerosis and fluorosis, result from a mutation in anion exchanger 1 gene (AE1) codes band 3.…”
Section: Introductionmentioning
confidence: 99%